Glutathione S-transferase Copy Number Variation Alters Lung Gene Expression - Butler, Marcus W. (2011)
BACKGROUND: The glutathione S-transferase (GST) enzymes catalyze the conjugation of xenobiotics to glutathione. Based on reports that inherited copy number variations (CNV) modulate some GST gene expression levels, and that the small airway epithelium (SAE) and alveolar macrophages (AM) are involved early in the pathogenesis of smoking-induced lung disease, we asked: do germline CNVs modulate GST expression levels in SAE and AM? METHODS: Microarrays were used to survey GST gene expression in SAE and AM obtained by bronchoscopy from current smokers and nonsmokers, and to determine CNV genotypes. RESULTS: Twenty six % of subjects were null for both GSTM1 alleles, with reduced GSTM1 mRNA levels seen in both SAE and AM. Thirty % of subjects had homozygous deletions of GSTT1 with reduced mRNA levels in both tissues. Interestingly, GSTT2B, exhibited homozygous deletion in blood in 27% of subjects and was not expressed in SAE in the remainder of subjects but was expressed in AM of heterozygotes and wild type subjects, proportionate to genotype. CONCLUSIONS: These data show a germline CNV-mediated linear relationship of genotype to expression level suggesting minimal compensation of gene expression levels in heterozygotes consistent with GST polymorphisms playing a role in the risk of smoking-associated xenobiotic-induced lung disease.